Quality Management Practices and MSME Performance: A Competitive Advantage Perspective - Yuni Pambreni; Alfi Maghfuriyah (Global Research Collaboration, 2026)
This research uses path analysis to analyze the implementation of Total Quality Management (TQM) through competitive advantage in improving the performance of MSMEs in the F&B sector in Boyolali Regency. Total Quality Management (TQM) as an independent variable with indicators namely customer focus, strategy-based, scientific approach, obsession with quality, teamwork, long-term commitment, continuous process improvement, freedom through control, education and training, employee involvement and empowerment, and unity of purpose. The intervening/mediation variable in this study is competitive advantage with indicators of innovation, differentiation, and leading in terms of low costs. Then the dependent variable is MSME performance with indicators of financial performance, consumer performance/customer satisfaction, internal/operational business process performance, and learning and growth. Primary data was obtained using a questionnaire as a research instrument, and processed using SPSS 23. The unit of analysis of this study is the owners and employees of MSMEs in the F&B sector in Boyolali Regency. The population number based on data from the Boyolali Regency Statistics Agency in 2023 is 292,182. Meanwhile, the number of samples will be calculated using the Slovin formula with the convenience sampling technique. The finding demonstrate that TQM exerts a significant positive effect on both competitive advantage and performance of food and beverage MSMEs. Furthermore, competitive advantage is found to have significant positive impact on MSME performance, indicating the strategic role of competitive advantage in improving business performance.